2018
DOI: 10.1038/s41598-018-35643-6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Zika virus neutralizing antibodies in normal healthy Thais

Abstract: Zika virus (ZIKV) infections have been reported from all over Thailand, but the number of reported cases remains low, suggesting a degree of immune protection against ZIKV infection. To address this possibility, the presence of ZIKV neutralizing antibodies was determined in serum from 135 healthy Thai adults with a plaque reduction neutralization test (PRNT), and a number of samples were subsequently analyzed for the presence of neutralizing antibodies to dengue virus (DENV) and Japanese encephalitis virus (JE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
33
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 57 publications
6
33
1
Order By: Relevance
“…10 Our results, combined with those from a survey among healthy Thais in Central Thailand (seroprevalence of 70.4%), suggest that this Thai population were only partially protected by the antibody. 20 These levels of immunity may explain the low but sustained level of ZIKV transmission in Thailand as proposed by previous authors (Ruchusatsawat et al, 2019). 28 Our results showed that older age is associated with seropositivity.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…10 Our results, combined with those from a survey among healthy Thais in Central Thailand (seroprevalence of 70.4%), suggest that this Thai population were only partially protected by the antibody. 20 These levels of immunity may explain the low but sustained level of ZIKV transmission in Thailand as proposed by previous authors (Ruchusatsawat et al, 2019). 28 Our results showed that older age is associated with seropositivity.…”
Section: Discussionmentioning
confidence: 65%
“…ZIKV was believed to be endemic in the Southeast Asia region for many years. 12,20,26,27 However, regardless of the nature of the source, one-half to one-third of the population are at risk of infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Our results, combined with those from a survey among healthy Thais in Central Thailand (seroprevalence of 70.4%[PRNT50≥10] and 20.2%[PRNT90≥20]), suggest that this Thai population were only partially protected by the antibody. 24 These levels of immunity may explain the low but sustained level of ZIKV transmission in Thailand as proposed by previous authors (Ruchusatsawat et al, 2019). 33 Our results showed that older age is associated with seropositivity.…”
Section: Discussionmentioning
confidence: 65%
“…A neutralization titer ≥1:10 by PRNT90 was considered as a seropositive. 23,24 Random samples of 10 positive (PRNT90 titers> 1:10) and 10 negative (PRNT90 titer < 1:10) serum samples were used to further test for neutralizing antibody against dengue virus (DENV) serotype 1-4…”
Section: Laboratory Testsmentioning
confidence: 99%